An Introduction to Regge Theory and High Energy Physics - Collins, P.D.B (Cambridge University Press, 1977)
This book presents an extended introduction to the theory of hadrons, the elementary particles that occur in the atomic nucleus. The main emphasis is on the theory of the complex angular momentum plane 'Regge theory'. In 1959 Tullio Regge demonstrated that it is useful to regard angular momentum as a complex variable when discussing solutions of the Schrödinger equation for non-relativistic potential scattering. This theory helps to classify the many different particles we know of, to explain the forces between them and to predict the results of high-energy scattering experiments. Regge theory thus serves as a unifying concept drawing together many different features of high-energy physics. This monograph is intended primarily for research students just beginning in particle physics, but experienced practitioners will also find much of interest.